2020
DOI: 10.1039/d0gc00979b
|View full text |Cite
|
Sign up to set email alerts
|

Achieving visible light-driven hydrogen evolution at positive bias with a hybrid copper–iron oxide|TiO2-cobaloxime photocathode

Abstract: H2 is an environmentally-friendly fuel that would allow for a circular economy but its sustainable production from solar energy and water using stable, efficient and scalable Earth-abundant materials, remains a challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Schematic representation of a cobaloxime-functionalized CuFe x O y . Adapted from ref . Copyright 2020 Royal Society of Chemistry.…”
Section: Examples Involving Solid-state Photocathodes Modified With M...mentioning
confidence: 99%
See 1 more Smart Citation
“…Schematic representation of a cobaloxime-functionalized CuFe x O y . Adapted from ref . Copyright 2020 Royal Society of Chemistry.…”
Section: Examples Involving Solid-state Photocathodes Modified With M...mentioning
confidence: 99%
“…Efficiency, cost/scalability, and durability are required features for large-scale, global implementation of solar-to-fuel technologies, and promising strategies for imparting these properties are highlighted in this review. These include examples of using semiconductors with relatively narrow band gaps to promote effective light absorption across the solar spectrum (refs , , , , , , , , , , , , and ), modulating the surface of the semiconductors with ions or molecular dipoles for directing interfacial energetics and charge transfer efficiencies, ,,, protecting the surface of semiconductors with stable overcoating layers to increase stability during photo­electrochemical operation (refs , , , , , , , , , , , , , , , , , and ), increasing the surface loadings of catalysts via leveraging nanostructured materials or overlayers (refs , , , , , , , , , and ), and passivating surface states (i.e., electronic states found at the surface of materials) via chemisorption with the aim of suppressing surface recombination. ,,,,,,− Despite these advances, an artificial photosynthetic construct has yet to effectively demonstrate all three of the desirable properties illustrated in Figure . Looking forward, outstanding research opportunities and questions in the areas of artificial photosynthesis and solar fuels include: What are the dominant interactions across length and timescales that control the performance of molecular-modified semiconductors and hierarchical materials? How can the molecular science of...…”
Section: Critical Analysis Conclusion and Outlookmentioning
confidence: 99%
“…The photocurrent stability of p-Si|TiO 2 |CoPy-4-L-HA photocathodes is superior to that of most reported hybrid photocathodes modified by the cobaloxime catalyst and its derivatives. [13,[26][27][28][29][30]32,56] The incident photon-to-current efficiency (IPCE) of the p-Si|TiO 2 |CoPy-4-(CHCH) 2 -HA electrode is higher than 10% (10.1-12.5%) in the range of 430-800 nm (Figure 6b). The charges passed through the circuit was 5.5C during 2.8 h of CPP experiment of the p-Si|TiO 2 |CoPy-4-(CHCH) 2 -HA electrode at 0 V, and meanwhile the gas chromatography analysis of the gaseous phase of the sealed PEC cell showed that 25 µmol cm −2 of H 2 was evolved from the photocathode.…”
Section: Stability and Efficiency Of P-si|tio 2 |Copy-4-l-ha Photocathodesmentioning
confidence: 99%
“…In recent years, the development of narrow bandgap semiconductor/molecular catalyst (SC/MC) hybrid photoelectrodes has attracted extensive attention. [7][8][9][10][11] In the reported SC/MC photocathodes, the narrow bandgap semiconductors of p-Si, [12][13][14][15][16][17][18][19][20][21][22][23] InP, [6,24] GaP, [25][26][27][28][29][30] GaInP 2 , [31] and CuFe x O y [32] were employed as light harvesters, and DuBois' nickel complexes, [13,[17][18][19][20] cobaloximes, [13][14][15][16][26][27][28][29][30][31][32][33] cobalt and iron porphyrin complexes, [25] cobalt tetraazamacrocyclic complex, [23] and cubane-like Mo 3 S 4 clusters [21,22]...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation